Bottom‐Up Designed Porous Coaxial Twin‐Electrodes for Efficient Redox Cycling (Adv. Funct. Mater. 7/2023). (9th February 2023) - Šafarik, Tatjana; Karajić, Aleksandar; Reculusa, Stéphane; Bartlett, Philip N.; Mano, Nicolas; Kuhn, Alexander
Abstract : Bottom‐Up Designed Porous Coaxial Twin‐Electrodes In article number 2210638, Alexander Kuhn, and co‐workers describe the redox cycling of molecules between two macroporous electrodes having a co‐axial architecture. The bottom‐up designed device, with easily tunable parameters, such as the gap, thickness and pore size of the individual electrodes, allows a significant signal enhancement, opening interesting perspectives for the development of miniaturized fully integrated electrochemical (bio)sensing systems. Cover design by Matija Cabadaj and In‐Seong Jo.